Nilai-Nilai Moral dalam Film Budi Pekerti - Nabila Dinan Farisa; Eka Yusup; Nurkinan Nurkinan (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
This study explores the representation of moral values in the movie Budi Pekerti using Roland Barthes' semiotic theory. The film portrays various moral challenges in the digital era, such as cyberbullying and the erosion of ethical behavior on social media, through the story of a main character who faces a personal moral crisis. The objectives of this research are to identify the moral values depicted in the film through the levels of denotation, connotation, and myth. A qualitative descriptive method was employed, with semiotic analysis used to interpret visual signs and dialogues in the film. The findings reveal six key moral values reflected in the narrative: (1) upholding justice, (2) honesty in speech, (3) moral courage, (4) mutual assistance, (5) realism and critical thinking in facing situations, and (6) responsibility. These values are analyzed not only as literal messages but also as social symbols that reflect contemporary societal issues. The study concludes that Budi Pekerti effectively conveys profound moral messages through its strong narrative and symbolic structure.